2014
DOI: 10.1002/pat.3275
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polyethersulfone/silver nanocomposite ultrafiltration membrane for antibacterial applications

Abstract: Antimicrobial ultrafiltration membranes were prepared by coating silver nanoparticles on the surface of polyethersulfone (PES) membranes which were fabricated via phase inversion induced by the immersion precipitation technique, and their morphology and performance were compared with the antimicrobial PES membranes synthesized by adding the silver nanoparticles into the casting solution during the phase inversion process. For this purpose, stable and uniform colloidal solutions of the silver nanoparticles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…[11,12] Some of these materials, specifically silver-based additives, are already commercially available and are applied for food packaging. [13,14] However, the increasing consumer health concern and growing demand for healthy foods have stimulated the use of natural biopreservatives, such as essential oils, e.g. carvacrol and thymol.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Some of these materials, specifically silver-based additives, are already commercially available and are applied for food packaging. [13,14] However, the increasing consumer health concern and growing demand for healthy foods have stimulated the use of natural biopreservatives, such as essential oils, e.g. carvacrol and thymol.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Some of these materials, specifically silver-based additives, are already commercially available and are applied for food packaging. [13,14] In recent years, polymer nanocomposites [15][16][17][18][19][20][21] containing metal oxide nano particles have been extensively studied for food packaging applications. [22] In particular, these nanocomposites exhibit excellent barrier properties, which are ascribed to the clay layers, hindering the diffusing molecule pathway.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Ag is believed to be less harmful to human living tissue than bacteria . Extensive efforts have been devoted to develop high‐performance UF membranes with the aid of Ag nanoparticles, and we found that Ag–polymer hybrid membranes possess improved hydrophilicity, permeability, protein‐fouling resistance, and antibacterial properties . It has also been reported that Ag particles with smaller sizes exhibit higher antibacterial activities and can impart hybrid membranes better biofouling resistance .…”
Section: Introductionmentioning
confidence: 57%
“…8,9 Extensive efforts have been devoted to develop highperformance UF membranes with the aid of Ag nanoparticles, and we found that Ag-polymer hybrid membranes possess improved hydrophilicity, permeability, protein-fouling resistance, and antibacterial properties. 8,[10][11][12][13][14][15][16][17] It has also been reported that Ag particles with smaller sizes exhibit higher antibacterial activities and can impart hybrid membranes better biofouling resistance. 18 However, practical applications are still hindered by several issues, including the leaching of Ag nanoparticles, the excessive release of toxic Ag ions from the oxidation of Ag, and the easy aggregation of Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%